Congenital knee dislocation with underlying arthrogryposis - Kamisan, Norazian; Zahari, Anis Anwar; Ismail, Imma Isniza (2024)
Congenital knee dislocation is a rare condition with an unknown etiology. It can be associated with syndromes or occur as an isolated condition. The severity of the deformity determines the treatment approach, ranging from conservative methods like casting to surgical correction. This report describes the case of a newborn with a grade III knee dislocation treated with serial casting.